ANALYZING THE EFFECT OF CELEBRITY ENDORSEMENT AND BRAND CREDIBILITY ON BRAND LOYALTY (A STUDY ON NIKE SHOES IN MANADO) - Loei, Fritz Wijaya (Jurnal Berkala Ilmiah Efisiensi, 2016)
Today, shoes became the important part of fashion. It is like the identity of people in daily life. Shoes has created a big opportunities for footwear company to getting high market share. In Indonesia, the competition in footwear industry is getting tight and variety. The study aims to analyze the effect of celebrity endorsement and brand credibility on brand loyalty of Nike Shoes in Manado. This research is causal type of research which uses primary data obtained through questionnaires and uses multiple regression analysis. 30 respondents/customers out of the population were surveyed as samples. The result shows celebrity endorsement has not partially affects on Brand Loyalty and brand credibility has partially affect on brand loyalty. Nike shoes company should more intensively and still use celebrity endorsement, even It’s has no significant effect to brand loyalty. Nike shoes company should keep improve their product.